2021
DOI: 10.1101/2021.02.25.432821
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impaired activation of Transposable Elements in SARS-CoV-2 infection

Abstract: Transposable elements (TEs) are induced in response to viral infections. TEs induction triggers a robust and durable interferon (IFN) response, providing a host defense mechanism. Still, the connection between SARS-CoV-2 IFN response and TEs remained unexplored. Here, we analyzed TE expression changes in response to SARS-CoV-2 infection in different human cellular models. We find that compared to other viruses, which cause global upregulation of TEs, SARS-CoV-2 infection results in a significantly milder TE re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 82 publications
1
5
0
Order By: Relevance
“…Another important supporting evidence is that our analysis of RNA-seq data of acute patients showed activation of the cGAS-STING pathway (see Figure 1B for cGAS upregulation in acute patients) which can be triggered by upregulation of retrotransposon-derived cytoplasmic DNA ( Decout et al, 2021 ). Interestingly, a recent preprint manuscript showed that viral load of SARS-CoV-2 was positively correlated with TE upregulation ( Sorek et al, 2021 ), and this is in agreement with our result that TE activation was positively correlated with COVID-19 severity at the recovery stage. However, the study also showed that TE activation was relatively mild during SARS-CoV-2 infection, and this may be partially explained by the cGAS-STING pathway which can be activated upon SARS-CoV-2 infection and may be responsible for the degradation of cytoplasmic retrotransposon-derived DNA to inactivate retrotransposons.…”
Section: Discussionsupporting
confidence: 92%
“…Another important supporting evidence is that our analysis of RNA-seq data of acute patients showed activation of the cGAS-STING pathway (see Figure 1B for cGAS upregulation in acute patients) which can be triggered by upregulation of retrotransposon-derived cytoplasmic DNA ( Decout et al, 2021 ). Interestingly, a recent preprint manuscript showed that viral load of SARS-CoV-2 was positively correlated with TE upregulation ( Sorek et al, 2021 ), and this is in agreement with our result that TE activation was positively correlated with COVID-19 severity at the recovery stage. However, the study also showed that TE activation was relatively mild during SARS-CoV-2 infection, and this may be partially explained by the cGAS-STING pathway which can be activated upon SARS-CoV-2 infection and may be responsible for the degradation of cytoplasmic retrotransposon-derived DNA to inactivate retrotransposons.…”
Section: Discussionsupporting
confidence: 92%
“…For example, various RNA viruses, including influenza, activate TLR4 (21), and although they do not contain DNA, they can, unexpectedly, activate and/or express inhibitors for the cGAS/STING pathway (62,63). IAV infection has previously been shown to induce LINE1 expression (64,65). We therefore tested the effect of manipulating the mechanism of innate immune amplification, that we have described, on IAV infection.…”
Section: Transposable Element Expression Restricts Rna Virus Infectionmentioning
confidence: 98%
“…also trigger cGAS/STING sensing, and SARS-CoV2 at least has been demonstrated to induce LINE1 expression(65,83). Concordantly, RNA viruses influenza (84), SARS-CoV(85,86), SARS-CoV2 (87), Porcine epidemic diarrhea virus (88), Dengue virus (89), Yellow fever virus (90), Zika virus(91), and Hepatitis C virus (92) all inhibit the cGAS/STING DNA sensing pathway.…”
mentioning
confidence: 99%
“…The study revealed that expression of HERV‐W in COVID‐19 patients correlated with disease outcome suggesting utilizing of HERVs as biomarkers for viral infection. Moreover, HERVs were up‐regulated in a human cell line after SARS‐CoV‐2 infection and bronchoalveolar lavage fluid of COVID‐19 patients 40,41 …”
Section: Hervs Are Involved In Viral Infectionsmentioning
confidence: 99%
“…Moreover, HERVs were up-regulated in a human cell line after SARS-CoV-2 infection and bronchoalveolar lavage fluid of COVID-19 patients. 40,41…”
Section: Hervs Associated With Rna Viral Infectionsmentioning
confidence: 99%